Environmental change between 1980 and 2020 followed by societal change in the Gulf of Gdańsk, Southern Baltic, a review - Węsławski, Jan Marcin; Urbański, Jacek; Piwowarczyk, Joanna; Kotwicki, Lech; Piskozub, Jacek; Kuliński, Karol; Pazdro, Ksenia; Wiktor, Józef; Sagan, Sławomir; Psuty, Iwona; Walczowski, Waldemar; Koroza, Aleksandra (Frontiers in Earth Science, 2025)
The Gulf of Gdańsk belongs to the best-known marine areas in the Baltic, with regular environmental observations since mid-20th century. It covers the widest array of marine habitats in Polish Maritime areas (from large river mouth to Gdańsk Deep), shallow vegetated lagoon and stony reefs and the highest resources of species diversity (about 400 Metazoa and over 300 Protista species). The area was also important as a fishing ground as well as a key site for the marine industry, shipping and tourism. The review of the changes in the Gulf of Gdańsk over last 40 years shows that it follows some of the global trends (increase in temperature, storminess, sea level rise, decrease in ice and oxygen), while the specific local phenomena like eutrophication and contamination are more difficult to assess (e.g., strong reduction in nutrient discharge did not change the levels of P and N in the system). After recovery from the environmental crisis in the 1980s, the toxic compounds in sediment and seawater are below the accepted thresholds. The reduction in some toxins resulting from better management (e.g., Mercury or chlorinated compounds) is blurred by the negative effects of climate warming (expansion of anoxic sediments) and contamination connected with its biogeochemical activity. Formerly degraded coastal habitats are recovering (especially seagrass), while the commercial fish catch collapsed, likely caused by the large-scale phenomena (climate warming), not directly connected with the local conditions of the Gulf. The societal use of the Gulf changed from industrial/fishery to largescale tourism and service, with fast growing pressure for coastline urbanization. The key phenomena (drivers of events) of the area include eutrophication, industrialization and biodiversity recovery.